Hubungan Inflasi, Jumlah Uang Beredar, dan Pendapatan Nasional Terhadap Strategi Perekonomian Indonesia - Nayla Ahlami Dalimunthe; Cintya Putri Nasution; Suaini Mebia Putri (Universitas 45 Surabaya, 2025)
This study aims to determine the relationship between inflation, money supply, and national income and their impact on Indonesia's economic strategy. The research method used in this study is descriptive research using a qualitative approach based on literature studies. Using this method, this study examines how these three variables influence each other in the context of the Indonesian economy. The results of the study show that inflation as an indicator of rising prices of goods and services has a close relationship with the amount of money in circulation and national income. An increase in the money supply tends to increase inflation, and higher national income can positively affect consumption and inflation rates. This relationship illustrates the importance of integrated monetary and fiscal policies to maintain economic stability.